Marketing Strategy in The Post Covid-19 Pandemic Period at Warkuy Coffee - Rezka Aida Patriasti Seja Purnama Ningsih; Natasya Aprillia Ernanda (International Journal of Travel, Hospitality and Events, 2024)
Purpose : The purpose of this study is to identify products, prices, places, promotions offered by Warkuy Coffee during the Covid-19 pandemic. Research Metods: The type of research used in this study is quantitative research. Quantitative research methods are one type of research whose specifications are systematic, planned and clearly structured from the beginning to the creation of the researcher's design. by using the unit of analysis, namely Warkuy Coffee. The data collection technique used in this study is to use primary data in the form of observation, interviews, questionnaire dissemination and skunk data in the form of books, company data and journals. Result and discussion: Warkuy Coffee is on Quadrant I in the Aggressive Stategi. It shows that Warkuy Coffee's position is very strong and has a lot of chances. Proved by the data obtained from the administrator that there are still a lot of visitors every day. That requires improved management of other strategies inining its existence at Warkuy Coffee. Implication : From the results of the study, it can be stated that the theoretical implications concluded that the products, prices, places, promotions offered by Warkuy Coffee can be accepted by the wider community, especially Warkuy Coffee visitors aged 18-25 years.   Keywords: Strategy, marketing, coffee, covid-19